What Happened to China Development Bank's 3 Billion Loan to Ghana? - Thomas Chen (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2016)
In 2010, Ghana secured a 3 billion loan from the China Development Bank to finance urgently needed gas projects. Six years later the agreement still faces major setbacks. This policy brief explores the factors behind these developments, and it outlines four key lessons from this experience. First, the brief concludes that it is important to garner the support of all stakeholders before approving a large-scale loan project. Second, inconsistencies between the loan financing agreement and existing regulations might have been avoided if Ghana had consulted with a third-party such as the World Bank. Third, institutional capacity is key to overseeing major infrastructure projects. Finally, when external fiscal conditions are favorable, Ghana should build external and fiscal policy buffers to mitigate against inevitable cyclical price shocks.
Keywords: 330